2009
DOI: 10.1016/j.chemphyslip.2009.06.140
|View full text |Cite
|
Sign up to set email alerts
|

First total synthesis and antiprotozoal activity of (Z)-17-methyl-13-octadecenoic acid, a new marine fatty acid from the sponge Polymastia penicillus

Abstract: The first total synthesis for the (Z)-17-methyl-13-octadecenoic acid was accomplished in seven steps and in a 45% overall yield. The use of (trimethylsilyl)acetylene was key in the synthesis. Based on a previous developed strategy in our laboratory the best synthetic route towards the title compound was first acetylide coupling of (trimethylsilyl)acetylene to the long-chain protected 12-bromo-1-dodecanol followed by a second acetylide coupling to the short-chain 3-methyl-1-bromobutane, which resulted in higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…In fact, we have shown that the acid ( Z )-14-methyl-9-pentadecenoic acid, also a monounsaturated iso methyl-branched fatty acid, inhibits the human DNA topoisomerase I but at the higher concentrations of 500 µM (Carballeira et al, 2007). Therefore, the present findings corroborate our previous results that monounsaturated iso methyl-branched fatty acids are more effective towards the LdTopIB than the human DNA topoisomerase I (Carballeira et al, 2009). …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In fact, we have shown that the acid ( Z )-14-methyl-9-pentadecenoic acid, also a monounsaturated iso methyl-branched fatty acid, inhibits the human DNA topoisomerase I but at the higher concentrations of 500 µM (Carballeira et al, 2007). Therefore, the present findings corroborate our previous results that monounsaturated iso methyl-branched fatty acids are more effective towards the LdTopIB than the human DNA topoisomerase I (Carballeira et al, 2009). …”
Section: Resultssupporting
confidence: 92%
“…strain KM86-9B displayed topoisomerase I inhibitory activity (Lee et al, 1998). In fact, we have also shown that the acid ( Z )-14-methyl-9-pentadecenoic acid inhibits the human placenta DNA topoisomerase I enzyme at concentrations of 500 µM (Carballeira et al, 2007), while the marine fatty acid ( Z )-17-methyl-13-octadecenoic acid inhibits the leishmania DNA topoisomerase IB enzyme at concentrations of 50 µM (Carballeira et al, 2009). The latter report indicated that these iso monounsaturated fatty acids do have antiprotozoal potential.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Un autre isomère, le nouvel acide 17-méthyl-13(Z)-octadécènoïque a été récem-ment caractérisé chez P. penicillus (Denis et al, 2009). C'est l'acide iso-ramifié nonadécènoïque avec la double liaison la plus proche de l'extré-mité de la chaîne, en n-5, et il a été obtenu par synthèse organique en raison de son activité contre le protozoaire Leishmania (Carballeira et al, 2009). Cette observation est renforcée par le fait que ce dernier AG semble provenir d'un allongement dicarboné de la chaîne de l'acide bactérien 15-méthyl-11(Z)-hexadé-cènoïque isolé de plusieurs sources, mais surtout chez Myxococcus xanthus (Boon et al, 1977 ;Reyes et Carballeira, 1996).…”
Section: Ag Mono-insaturés Et Ramifiésunclassified
“…We had previously shown that the iso methyl-branched monounsaturated fatty acid ( Z )-17-methyl-13-octadecenoic acid displays antileishmanial activity towards Leishmania donovani promastigotes with an EC 50 = 19.8 ± 7.0 µg/ml and, as a probable intramolecular target, inhibits the leishmania DNA topoisomerase IB enzyme at concentrations of 50 µM 9. Given these previous results we decided to test the cis cyclopropane fatty acid 1b against L. donovani promastigotes and establish how cyclopropane substitution compares to monunsaturation in determining the antileishmanial activity of these iso -C 18 fatty acids 10.…”
mentioning
confidence: 99%